1996
DOI: 10.1149/1.1836961
|View full text |Cite
|
Sign up to set email alerts
|

Formic Acid Oxidation in a Polymer Electrolyte Fuel Cell: A Real‐Time Mass‐Spectrometry Study

Abstract: The electro-oxidation of formic acid was studied in a direct-oxidation polymer-electrolyte fuel cell at 170°C using real-time mass spectrometry. The results are compared with those obtained for methanol oxidation under the same conditions. Formic acid was electrochemically more active than methanol on both Pt-black and Pt/Ru catalysts. The polarization potential of formic acid oxidation was ca. 90 to 100 mV lower than that of methanol.The oxidation of formic acid was dependent on the water/formic acid mole rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(78 citation statements)
references
References 0 publications
0
76
0
2
Order By: Relevance
“…Nevertheless, an open circuit voltage around 0.6-0.7 V and a peak power of more than 0.2 W cm −2 have been achieved at 200 • C under atmospheric pressure. Ünsal et al [126,127] operated a DMFC using the commercial Celtec ® -V MEA based on PBI-PVPA membranes, showing higher OCV and better fuel cell performance than Nafion 117 at methanol concentrations above 1 M. Other types of fuels, for example, ethanol, 1-propanol, 2-propanol [241], trimethoxymethane [242] and formic acid [243] have also been investigated.…”
Section: Fuel Cell Performancementioning
confidence: 99%
“…Nevertheless, an open circuit voltage around 0.6-0.7 V and a peak power of more than 0.2 W cm −2 have been achieved at 200 • C under atmospheric pressure. Ünsal et al [126,127] operated a DMFC using the commercial Celtec ® -V MEA based on PBI-PVPA membranes, showing higher OCV and better fuel cell performance than Nafion 117 at methanol concentrations above 1 M. Other types of fuels, for example, ethanol, 1-propanol, 2-propanol [241], trimethoxymethane [242] and formic acid [243] have also been investigated.…”
Section: Fuel Cell Performancementioning
confidence: 99%
“…The flexibility and the performance implications of operating membraneless sodium perborate fuel cell (MLSPBFC) under "acid-alkaline media, " that is, one electrode is acidic and the other one is alkaline condition, will be the focus of this study. Recent catalysis and fuel cell research has indicated that formic acid may be a good alternative to the common fuels of hydrogen and methanol [7,8]. Even though formic acid has a lower energy density than methanol, 7.49 and 17.5 J/mL, respectively, the possibility for a significant increase in performance with the correct catalyst exists [9].…”
Section: Introductionmentioning
confidence: 99%
“…Purely fundamental reactions on single crystal electrode surfaces, including a determination of the surface coverage with a given species by electrodesorption and mass spectrometric detection, serve to build a link to similar studies in surface science (typically in UHV). Reactions at carbon supported nanoparticles were also studied [9,10], as well as decomposition reactions in nonaqueous solvents [11,12], and modifications of the technique allowed to study side products formed in batteries and fuel cells [13].…”
mentioning
confidence: 99%